Photocatalytic carbanion generation – benzylation of aliphatic aldehydes to secondary alcohols. Issue 19 (25th April 2019) - Donabauer, Karsten; Maity, Mitasree; Berger, Anna Lucia; Huff, Gregory S.; Crespi, Stefano; König, Burkhard
Abstract : We present a redox-neutral method for the photocatalytic generation of carbanions. Abstract : We present a redox-neutral method for the photocatalytic generation of carbanions. Benzylic carboxylates are photooxidized by single electron transfer; immediate CO2 extrusion and reduction of the in situ formed radical yields a carbanion capable of reacting with aliphatic aldehydes as electrophiles giving the Grignard analogous reaction product.